What Drives the Global “Land Rush”? - Arezki, Rabah; Deininger, Klaus; Selod, Harris (2012)
The 2007-2008 upsurge in agricultural commodity prices gave rise to widespread concern about investors causing a "global land rush". Large land deals can provide opportunities for better access to capital, transfer of technology, and advances in productivity and employment generation. But they carry risks of dispossession and loss of livelihoods, corruption, deterioration in local food security, environmental damage, and long-term social polarization that led some countries to recently pass legislation restricting foreign land acquisition. To stimulate evidence-based debate, this paper explores determinants of foreign land acquisition for large-scale agriculture. It quantifies demand for land deals, showing it focused on Africa where land expansion is about 20 times the level it was in the past. The analysis uses data on bilateral investment relationships, together with newly constructed indicators of agro-ecological suitability in non-protected and forested areas with low population density as well as land rights security. It estimates gravity models that can help identify determinants of foreign land acquisition dedicated to large-scale agriculture. The results confirm the central role of agro-ecological potential as a pull factor. In contrast to the literature on foreign investment in general, the quality of the business climate is insignificant, whereas weak land governance and tenure security for current users make countries more attractive for investors. Implications for policy are discussed.